Robotic vs. open surgery in obese women with low-grade endometrial cancer: comparison of costs and quality of life measures - Adi Sofer; Racheli Magnezi; Ram Eitan; Oded Raban; Orna Tal; Noam Smorgic; Zvi Vaknin (BMC, 2020)
Abstract Background This retrospective study compared perioperative measures, costs, quality of life and survival after open vs. robotic surgery, among obese women diagnosed with low-grade endometrial cancer. Methods Obese women (body mass index (BMI) ≥ 30) who underwent open or robotic surgery for endometrial cancer, in one of two tertiary medical centers in the center of Israel, 2013-2016, postoperative grade 1-2, were included. Costs per patient, including 30-days post-surgery were calculated. Quality of life was evaluated by Physical and Mental Components of the SF-36 and a recovery from surgery questionnaire. Overall survival outcomes were obtained from patients' files. Surgical outcomes, including operating and anesthesia times, length of hospital stay, and intraoperative and postoperative complications according to the Clavien-Dindo classification scale were reviewed. Results In all, 138 women with BMI ≥30 underwent open (n = 61) or robotic surgery (n = 77) during the study period. The groups had similar BMI, comorbidities, demographics and tumor characteristics. Robotic surgery was associated with shorter hospital stays (mean 1.7 vs. 4.8 days; P < .0001) and fewer postoperative complications (Clavien-Dindo > 2, 5.2% vs. 19.7%; P = .0008), but longer operating theater time (3.8 vs. 2.8 h; P < .001). Costs are equivalent when at least 350 robotic surgeries are performed annually, not including the initial system costs. Quality of life measures were better after robotic surgery. SF-36 showed better measures for robotic surgery (Physical 56 vs. 39 and Mental 73 vs. 56; P < .01). After robotic surgery, patients tended to recover quicker when compared to open surgery, as they returned to normal activities earlier, with less need for family and governmental assistance (mean recovery time, 23 vs. 70 days; P < 0.006 and mean change in preoperative total functioning score, − 1.5 vs. -3.9: P < 0.05, respectively). Overall, 5-year survival was 89.8% for the open surgery group vs. 94% for the robotic surgery group (log rank, P = 0.330). Conclusions Obese women with low-grade endometrial cancer had better quality of life after robotic vs. open surgery. They also had shorter hospital stays and fewer postoperative complications. Centers with high volumes of robotic surgery can achieve similar costs when comparing both methods. These results were achieved without jeopardizing survival. Our results further emphasize the need for the Israeli healthcare system to include specific reimbursement for robotic procedures in the population we studied.